2-Hydroxy-10-phenacylpyrrolo[2,1-c][1,4]benzodiazepine-5,11-dione - Ourahou, S.; Chammache, M.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(20)H(18)N(2)O(4), consists of a benzodiazepinedione system fused to a pyrrole system. The sevenmembered ring adopts a boat-shaped conformation (with the methine C atom as the prow); the five-membered ring adopts an enveloped-shaped conformation (with the hydroxybearing C atom as the flap). In the crystal, the hydroxy group is hydrogen bonded to the carbonyl O atom of an adjacent molecule, generating a zigzag chain.